Impact of Mycobacteroides abscessus colony morphology on biofilm formation and antimicrobial resistance - Anna Maria Oschmann-Kadenbach; Christoph Schaudinn; Leonard Borst; Carsten Schwarz; Katharina Konrat; Mardjan Arvand; Astrid Lewin (Elsevier, 2024)
Mycobacteroides abscessus is one of the most resistant bacteria so far known and causes severe and hard to treat lung infections in predisposed patients such as those with Cystic Fibrosis (CF). Further, it causes nosocomial infections by forming biofilms on medical devices or water reservoirs. An eye-catching feature of M. abscessus is the growth in two colony morphotypes. Depending on the presence or absence of glycopeptidolipids on the cell surface, it forms smooth or rough colonies. In this study, a porous glass bead biofilm model was used to compare biofilm formation, biofilm organization and biofilm matrix composition in addition to the antimicrobial susceptibility of M. abscessus biofilms versus suspensions of isogenic (smooth and rough) patient isolates. Both morphotypes reached the same cell densities in biofilms. The biofilm architecture, however, was dramatically different with evenly distributed oligo-layered biofilms in smooth isolates, compared to tightly packed, voluminous biofilm clusters in rough morphotypes. Biofilms of both morphotypes contained more total biomass of the matrix components protein, lipid plus DNA than was seen in corresponding suspensions. The biofilm mode of growth of M. abscessus substantially increased resistance to the antibiotics amikacin and tigecycline. Tolerance to the disinfectant peracetic acid of both morphotypes was increased when grown as biofilm, while tolerance to glutaraldehyde was significantly increased in biofilm of smooth isolates only. Overall, smooth colony morphotypes had more pronounced antimicrobial resistance benefit when growing as biofilm than M. abscessus showing rough colony morphotypes.